Pengaruh Model Pembelajaran Probing Prompting Terhadap Hasil Belajar Siswa Pada Materi Segiempat - Risnawati Manoppo; Sarson W. Dj. Pomalato; Siti Zakiyah; Melisa Mutiara Lestari Puloo (Jambura Journal of Mathematics Education, 2022)
This article discusses the Effect of the Probing Prompting Learning Model on Students’ Learning Outcomes in a Rectangular topic to know the differences in learning outcomes of students whose learning uses the Probing Prompting Learning Model and learning outcomes of students whose learning uses the direct Learning Model in Rectangular topic. The method used is an experimental design with a pretest-posttest control group design. The sampling technique used cluster random sampling and the technique of data collection through tests in the form of essays. The result of the research showed that there were differences in learning outcomes of students whose learning uses the Probing Prompting Learning Model and learning outcomes of students whose learning uses the direct Learning Model, whereas learning outcomes of students whose learning uses the Probing Prompting Learning Model were higher than learning outcomes of students whose learning uses direct Learning Model in Rectangular Topic. Probing prompting can guide students to express their ideas so that a process of thinking can generate each student's knowledge and experience.